2011
DOI: 10.1007/s00520-011-1233-6
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ morbidity in palliative care unit: predicting by gender, age, burden and self-esteem

Abstract: A high prevalence of morbidity was noticed in caregivers of patients admitted at the palliative care unit. The early provision of psychological support to caregivers by healthcare staff may indeed help to decrease comorbidity symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
(44 reference statements)
3
42
1
4
Order By: Relevance
“…These rates are comparable to previous studies, e.g., a study of CostaRequena and colleagues who reported a proportion of 76% of anxiety and 77% of depression in 159 family caregivers of patients in a palliative care unit. 1 In our study, prevalence and intensity of anxiety and depression in caregivers correlated significantly with each other and were independent of caregivers' gender. There was a clear trend towards higher symptom distress among male caregivers.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These rates are comparable to previous studies, e.g., a study of CostaRequena and colleagues who reported a proportion of 76% of anxiety and 77% of depression in 159 family caregivers of patients in a palliative care unit. 1 In our study, prevalence and intensity of anxiety and depression in caregivers correlated significantly with each other and were independent of caregivers' gender. There was a clear trend towards higher symptom distress among male caregivers.…”
Section: Discussionmentioning
confidence: 84%
“…Concerning caregiver's gender, a study by Grov and colleagues had suggested a significant impact of female gender on the caregiver's depression, 3 whereas CostaRequena and colleagues had demonstrated a higher impact of caregivers' self-esteem and distress than of sociodemographic factors such as caregiver gender or age. 1 The impact of the relationship between patients and caregivers has rarely been investigated in previous studies. Palos and colleagues have reported significantly higher symptom levels in family members compared to nonfamily caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of the educational support for the caregivers of cancer patients (Belgacem et al, 2013), caregivers who did not receive educational intervention reported a ZBI score of 31.4 ± 14.9. Considering the low burden score of 16.0 ± 9.9 among those who received the educational program (Belgacem et al, 2013), and burden scores in the range of 17.0e23.2 among caregivers receiving palliative care (Costa-Requena et al, 2012;Grunfeld et al, 2004;Higginson and Gao, 2008;Higginson et al, 2010), the considerable caregiving burden being experienced by caregivers participated in this study which could to be relieved by additional support. It is of note that 88.4% of the participants of this study were caregivers of patients without or with minimal functional change, nonetheless substantial burden was expressed by the caregivers.…”
Section: Discussionmentioning
confidence: 99%